Pengaruh Tinggi Pemotongan Terhadap Kecernaan In Vitro Bahan Kering dan Bahan Organik serta Total Digestible Nutrient (TDN) Rumput Gajah Mini (Pennisetum purpureum cv. Mott) Panen Kedua - Wisang, Roinaldo; Djoko Sulistijo, Edi; P. Nastiti, Herayanti (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2025)
The aim of this study was to determine the effect of cutting height on the in vitro digestibility of dry matter and organic matter, as well as total digestible nutrients (TDN), in elephant grass (Pennisetum purpureum cv. Mott). A completely randomized design (CRD) was used with five treatments and three replications. T1 was a cutting height of 5 cm above ground level, T2 was a cutting height of 10 cm above ground level, T3 was a cutting height of 15 cm above ground level, T4 was a cutting height of 20 cm above ground level, and T5 was a cutting height of 25 cm above ground level. The in vitro digestibility of dry matter and organic matter, as well as total digestible nutrients (TDN), was investigated. Data were analyzed using analysis of variance (ANOVA). The results of the analysis of variance showed that the in vitro digestibility of dry matter, organic matter, and total digestible nutrients (TDN) of Pennisetum purpureum cv. Mott was not affected by cutting height (P>0.05). The results showed that cutting height had a similar effect on dry matter, organic matter, and TDN. At a cutting height of 5 cm above the ground, the average in vitro digestibility of dry matter, organic matter, and TDN was 72.429%, 71.865%, and 62.658%, respectively.